Green Synthesis of Reduced Graphene Oxide Using L-Cysteine as Reductant - Hassan A. Alshamsi (Journal of Global Pharma Technology, 2018)
Graphene-derived materials have been studied in many applications due to its excellent electrical, mechanical, and thermal properties .There remains a real need for the easy, eco-friendly and scalable preparation method of graphene due to various potential applications. Chemical reduction is the most versatile method for the large scale production of graphene. Here we report the operating conditions for a one-step, economical and green synthesis method for the reduction of graphene oxide using a bio molecule L-cysteine under mild reaction conditions. Characterizations of the resulting product have been done by thermo-gravimetric analysis, X-ray diffraction, FTIR, UV-visible spectroscopy, EDX spectrum and the morphology of the synthesized reduced graphene oxide (rGO) was examined by AFM, SEM and TEM.